Length of Day and geomagnetic field asymmetry: an observed correlation for the last three millennia - Puente-Borque, M. (2025)
The length of day (LOD) and the geomagnetic field are two geophysical phenomena closely linked to the dynamics of Earth's outer core. Fluid motion in the Earth's outer core drives variations in both the geomagnetic field and the core's angular momentum. While this relationship has been extensively studied at decadal and interannual scales, the evolution of the geodynamo unfolds over much longer periods. This study focuses on the millennial scale variations. Reconstructed LOD changes from ancient records of eclipses reveal an oscillatory component with a periodicity of approximately 1300 years and 4 ms of amplitude which cannot be explained by tidal effects, glacial isostatic adjustment or the ocean and atmospheric dynamics. Our analysis indicates that the non-tidal fluctuations in the LOD are correlated with the paleosecular variation of the Earth's magnetic field over the last three millennia. In particular, LOD maxima occur when the eccentric dipole shifts towards the Pacific region, signature of a more asymmetric geomagnetic field, while the geocentric dipole becomes more axial. Conversely, LOD minima correspond to a more centred eccentric dipole and a more tilted geocentric dipole towards Atlantic region. These results provide new insights into the coupling between Earth's rotation and geomagnetic field variations on millennial timescales.